Pengaruh Job Insecurity terhadap Turnover Intention Melalui Job Satisfaction sebagai Variabel Intervening pada Pekerja PKWT di PT. Bio Farma - Muhammad Arief Suhendra; Henry Anggoro Djohan; Cynthia Vanessa Djodjobo (POLITEKNIK KETENAGAKERJAAN, 2025)
This study aims to determine the effect of job insecurity on turnover intention with job satisfaction as an intervening variable in PKWT workers at PT. Bio Farma. The sampling technique used was probability sampling with a sample size of 76 respondents. The analysis was conducted using SEM (Structural Equation Modeling) measurements on Smart PLS 4.0. The results showed that job insecurity had a negative and significant effect on job satisfaction. Job insecurity had a positive and significant effect on turnover intention. Job satisfaction had a negative and significant effect on turnover intention. In addition, job insecurity had a positive and significant effect on turnover intention through job satisfaction as an intervening variable.